Psychiatric outpatients dropout: Causes and institutional context - Velázquez R., Alejandro (2000)
This study examined treatment permanence of psychiatric outpatients, and identified reasons expressed by dropouts for discontinuing treatment. The clinical records of 314 patients (177 female arid 137 male) were examined including a telephone follow-up on all former patients who could be found (64). The retrospective analysis spanned up to seven years after dropout. Results revealed a cumulative dropout percentage greater than 70% without identifiable trends attributable to patient gender, age, or place of residence. Diagnostic categories showed slightly higher but inconsistent dropout by "organic" patients. The most frequent reasons for stopping treatment included: feeling better (19.6% ), receiving treatment elsewhere ( 17.4% ), lacking financia! resources (10.9%), non-typified reasons (7.6%), medication side effects (6.5%), and caregiver rudeness (6.5%). Results emphasize the need for effective psychological interventions designed to both improve institutional quality of treatment and promote treatment compliance.